Electron Paramagnetic Resonance Spectroscopy - Carlos Calle; Sabine Van Doorslaer; Stefan Stoll; Zoltan Mádi; Lorenz Liesum; Walter Lammler; Moritz Kälin; Jeffrey Harmer; Willi Groth; Igor Gromov; Josef Granwehr; Jörg Forrer; et al. (CHIMIA, 2001)
A survey of the activities of the EPR group at ETH is given. The different research areas are discussed briefly and a particular project is highlighted.